Analisis Penerapan Program Sekolah Penggerak terhadap Prestasi Belajar Siswa Tingkat Sekolah Dasar (SD) Se-Kotamadya Binjai - Tioria Pasaribu; Achmad Fauzi; Zira Fatmaira (Journal on Education, 2024)
“Sekolah Penggerak” Program is a program to encourage the transformation process of educational units to realize the Pancasila student profile which was launched online on February 1 2021. The city of Binjai was chosen to implement this program during the 2nd Generation of Mobilization School. And there were 14 schools selected, namely 2 Kindergarten schools (TK), 8 Elementary Schools (SD), 2 Middle Schools (SMP), and 2 High Schools (SMA). Among the selected school levels, only the Elementary School (SD) level was selected more often than the others. So the proposer is interested in analyzing the implementation of the “Sekolah Penggerak” program in 8 elementary schools (SD) throughout Binjai Municipality and collecting the learning achievements that have been obtained by students. From the research results, it was found that students were more motivated and enthusiastic in learning. This is because the learning programs in the “Sekolah Penggerak” program are interesting and more fun. Students are invited to be more active and creative in learning through innovative learning models. Thus, this research intends to provide information to other education providers regarding the achievement of activities and learning achievements of students in the “Sekolah Penggerak” program in the Binjai Municipality so that they can motivate other schools to participate in implementing the “Sekolah Penggerak” program. In this way, it is hoped that this research will be useful for teachers and other educational institutions.